The Effectiveness of Practicum-Based Learning in Improving Students’ Learning Outcomes in Fiqh Ibadah and Practice Courses - Nurjali (Zabags International Journal of Education, 2026)
Fiqh Ibadah learning in higher education is often dominated by theoretical approaches that provide limited hands-on experience for students, resulting in suboptimal learning outcomes and insufficient practical competence in performing religious practices. This study aims to analyze the effectiveness of practicum-based learning in improving students’ learning outcomes in the Fiqh Ibadah and Practice course. This research employed a quantitative approach using a classroom action research design conducted in two cycles, involving students of the PGMI Study Program at Institut Islam Al-Mujaddid Sabak as research participants. Data were collected through learning outcome tests, student activity observations, and learning documentation, while data analysis utilized descriptive statistics to measure improvements in mean scores and learning mastery percentages. The findings indicate that the implementation of practicum-based learning gradually improved students’ learning outcomes from the pre-cycle to the second cycle, accompanied by increased learning engagement and student participation during the instructional process. These results demonstrate that practicum-based learning provides more meaningful learning experiences and enhances both conceptual understanding and practical skills. This study contributes to the development of more applicable Fiqh Ibadah instructional strategies and offers practical implications for lecturers in improving the quality of Islamic education in higher education institutions.